PENGARUH MODEL PEMBELAJARAN DAN POLA ASUH ORANG TUA TERHADAP HASIL BELAJAR IPS - Wahyuddin; Suyitno Muslim; Khaeruddin (Jurnal Tunas Bangsa, 2020)
This study aims to determine the effect of learning models and parenting styles on social studies learning outcomes in grade V of elementary school. This study uses factorial design 2x2. The sample consisted of 56 students. The data analysis technique was the analysis of two-way variance (ANAVA) and continued with the Tuckey test at a significance level of α = 0.05. To test the normality of the data using the liliefors test and Homogeneity test using the barlett test. The results of this study indicate that 1) Social studies learning outcomes in the group of students who were taught using the Quantum Teaching model were higher than the Social Studies learning outcomes in the group of students who were taught using the Expository learning model. 2) Social studies learning outcomes of students who are cared for using a higher democratic pattern than students who are cared for using an authoritarian pattern. 3) There is an interaction effect between the learning model and parenting styles on student social studies learning outcomes. 4) Social studies learning outcomes of students who are cared for using democratic patterns and students who are taught using a higher Quantum Teaching model compared to students who are cared for using democratic patterns and students who are taught using the Expository learning model. 5) Social studies learning outcomes of students who are cared for using an authoritarian pattern and students who are taught using the Quantum Teaching model are lower compared to students who are cared for using an authoritarian pattern and students who are taught using the Expository learning model. 6) Social studies learning outcomes of students who are taught using the Quantum Teaching model on students raised using a democratic pattern higher than the social studies learning outcomes of students who are taught using the Quantum Teaching model and students who are cared for using an authoritarian pattern. 7) Social studies learning outcomes of students who were taught using the Espository learning model for students who were cared for using a democratic pattern was lower than the social studies learning outcomes of students who were taught using the Expository learning model and students who were cared for using authoritarian patterns. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran dan pola asuh orang tua terhadap hasil belajar IPS kelas V Sekolah Dasar. Penelitian ini menggunakan Desain factorial 2 x 2. Sampel terdiri dari 56 siswa. Teknik analisis data adalah analisis varians dua jalur (ANAVA) dan dilanjutkan dengan uji Tuckey pada tingkat signifikansi α = 0.05. Untuk menguji normalitas data menggunakan uji liliefors dan uji Homogenitas menggunakan uji barlett. Hasil penelitian ini menunjukkan bahwa 1) Hasil belajar IPS pada kelompok siswa yang dibelajarkan menggunakan model Quantum Teaching lebih tinggi dibandingkan hasil belajar IPS pada kelompok siswa yang dibelajarkan menggunakan model pembelajaran Ekspositori. 2) Hasil belajar IPS siswa yang diasuh menggunakan pola Demokratis lebih tinggi dibandingkan dengan siswa yang diasuh menggunakan pola Otoriter. 3) Terdapat pengaruh interaksi antara model pembelajaran dengan pola asuh orang tua terhadap hasil belajar IPS siswa. 4) Hasil belajar IPS siswa yang diasuh menggunakan pola demokratis dan siswa yang dibelajarkan menggunakan model Quantum Teaching lebih tinggi dibandingkan dengan siswa yang diasuh menggunakan pola demokratis dan siswa yang dibelajarkan menggunakan model pembelajaran Expositori. 5) Hasil belajar IPS siswa yang diasuh menggunakan pola otoriter dan siswa yang dibelajarkan menggunakan model Quantum Teaching lebih rendah dibandingkan dengan siswa yang diasuh menggunakan pola otoriter dan siswa yang dibelajarkan menggunakan model pembelajaran Expositori. 6) Hasil belajar IPS siswa yang dibelajarkan menggunakan model Quantum Teachingpada siswa yang diasuh menggunakan pola demokratis lebih tinggi dibandingkan dengan hasil belajar IPS siswa yang dibelajarkan menggunakan model Quantum Teaching dan siswa yang diasuh menggunakan pola otoriter. 7) Hasil belajar IPS siswa yang dibelajarkan menggunakan model pembelajaran Eskpositori pada siswa yang diasuh menggunakan pola demokratis lebih rendah dibandingkan dengan hasil belajar IPS siswa yang dibelajarkan menggunakan model pembelajaran Ekspositori dan siswa yang diasuh menggunakan pola otoriter. Kata Kunci: Model Pembelajaran, Pola Asuh Orang Tua, Hasil Belajar IPS